Pembagian harta hibah sebagai pengganti warisan di Desa Jatisari, Kecamatan Tempeh, Kabupaten Lumajang - Kamaliya, Firda Faroh (Maliki Interdisciplinary Journal, 2024)
The assets owned by parents will of course be the rights of their family members. This can also be called inheritance if the parents have died. Community practice assumes that assets distributed by parents to their children while the parents are still alive are referred to as inheritance. This research aims to determine the views of perpetrators of distributing gifted assets as a substitute for inherited assets and also to determine the practice of distributing gifted assets as a substitute for inherited assets in Jatisari Village, Tempeh District, Lumajang Regency. The type of research used is empirical research with a qualitative approach with the research location in Jatisari Village, Tempeh District, Lumajang Regency. The results of the research show that the majority of people in Jatisari Village think that gifted assets are the same as inherited assets because they are both assets given by parents to children. The practice carried out when dividing assets is to start with parents who are old and unable to carry out their activities properly, who then gather all their children and the parents immediately divide the assets equally among their children without paying attention to what share the children should get according to the law. Islam. This is due to the lack of public knowledge and also the level of education obtained is still relatively low, namely only elementary school graduates.